Effect of COVID-19 restrictions and fuel prices on traffic volume and offenses in Iran: A spatiotemporal analysis - Milad Delavary; Amir Hossein Kalantari; Hossein Farsangi; Abolfazl Mohammadzadeh Moghaddam; Ali Hadianfar; Ward Vanlaar; Martin Lavallière (PLoS ONE, 2025)
With the outbreak of the COVID-19 pandemic and the subsequent imposition of mobility restrictions in many nations, traffic volumes and driving behaviors have changed worldwide. This study aims to investigate the effect of COVID-19 restrictions and fuel prices on traffic volume and offenses (speeding, tailgating, and illegal overtaking) in Iran’s provincial and aggregated data in the study period of March 21, 2019, to May 20, 2020. A time-series analysis was conducted to capture the effects of interventions in level and trend, followed by a spatial autocorrelation of the interventions among provinces to identify the provinces that formed clusters in terms of traffic volume and offenses before and after each intervention. Most of the COVID-19 restrictions (and the pandemic itself) did not reduce traffic volume and rate of traffic offenses whereas an increase in fuel prices decreased traffic volume and offenses (except for illegal overtaking). Furthermore, traffic volume showed an increasing trend after the imposition of mobility restrictions, suggesting that preventive measures could not control intercity trips during the pandemic. Spatiotemporal analysis showed mobility restrictions effectively removed some provinces from the clusters with above-average volume, tailgating, and overtaking data. The possible reasons for these findings and potential solutions are discussed.